2006
DOI: 10.2114/jpa2.25.339
|View full text |Cite
|
Sign up to set email alerts
|

Time under Tension and Blood Lactate Response during Four Different Resistance Training Methods

Abstract: Mechanical stimuli have often been suggested to be the major determinant of resistance training adaptations; however, some studies suggested that metabolic changes also play an important role in the gains of muscle size and strength. Several resistance training methods (RTM) have been employed with the purpose of manipulating mechanical and metabolic stimuli; however, information about their physiological effects are scarce. The objective of this study was to compare the time under tension (TUT) and blood lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
2
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 33 publications
4
62
2
7
Order By: Relevance
“…Gentil et al [13] compared four different strength training methods using the same overload in the exercise leg extension. In the method with the traditional protocol of 10-RM, the speed of 2 s for the concentric phase and 2 s for the eccentric, there was a TUT total of 42.08 ± 3.18 s. This differs from the present study that found a much lower TUT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gentil et al [13] compared four different strength training methods using the same overload in the exercise leg extension. In the method with the traditional protocol of 10-RM, the speed of 2 s for the concentric phase and 2 s for the eccentric, there was a TUT total of 42.08 ± 3.18 s. This differs from the present study that found a much lower TUT.…”
Section: Discussionmentioning
confidence: 99%
“…These results can be justified because the execution speed was different between studies, which is as fast as possible and held in multi-joint exercise for the upper limbs. Gentil et al [13] also found that the speed of different execution protocols changes the number of repetitions performed, thus interfering directly with the TUT, holding the number of repetitions and the results, as there were found higher lactate levels in a smaller number of repetitions, but a higher TUT was generated compared to the traditional protocol. These results also suggest that the same number of repetitions may generate different TUT for different exercises and muscle groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All integrated exercises must be defined in aspects of movement velocity, range of motion and trained muscle groups to attain-specific effects. For example, existing resistance training methods (e.g., hypertrophy, inter-muscular coordination, maximum strength) trigger different acute physiologic and metabolic effects (GarciaManso et al 2012;Gentil et al 2006). At the point when the physiological systems have adapted to a given stimulus, higher challenges (difficulty, load intensity, volume) are required to achieve further improvements.…”
mentioning
confidence: 99%
“…The 10-MR sets evaluated in experiments of Augustsson et al 5 and Gentil et al 5 represented intensities significantly superior to sets performed at 30% and 60% of 1-MR 25 . This heavy overload induces a larger production of metabolites 18,26 and, therefore, causes a greater activation of muscular receptors sensible to biochemical disturbances, such as the afferent groups III and IV, the muscle spindles and the Golgi tendon organ [27][28][29] . Taking into account that these structures generate a sensorial feedback that reduces the recruitment capacity of the motor units 30 , it is possible that the low amplitude values of the electromyographic signal recorded during the multi-joint exercises analyzed by Augustsson et al 5 and Gentil et al 5 were due to inhibitory mechanisms initiated in the single-joint exercises.…”
Section: Discussionmentioning
confidence: 99%